Kinerja Organisasi Pelayanan Umum (Kasus Pelayanan KTP/KK dan Akta di Kantor Pelayanan Terpadu Kabupaten Sukoharjo Propinsi Jawa Tengah): Performance of Public Service Organization (Case of ID Card/ Family Card and Birth - Perpustakaan UGM, i-lib ([Yogyakarta] : Lembaga Penelitian dan Pangabdian kepada Masyarakat, Universitas Gadjah Mada, 2003)
The purpose of the research is to describe performance of ID Card/ Family Card and Birth Certificate Servise Office and the factors that influence the performance of ID Card/Family Card and Birth Certificate Service Office in Unified Service Office of Residence of Sukoharjo, the Province of Central Java. With consideration that the performance of this service office indicates good performance shown by characteristics such as simple procedures, fast service processes, high productuvity, responsive, the consistency to the rules and accountable. The variables that used by this research to define the performance of the service office are the structure of the organization, the technology used by the organization, the culture of the organization and the stakeholder bach-up of the organization. The fixation of these four based on theory considered as the definite variable of the performance of public service organization. To reach the purpose of the resesarch, the research method that used is descriptive-qualitative research analized by three channel activity : data reduction, data serving, and the drawn of conclusion done at the same moment through twist process. The data gained from field observation, document study and inteviev with key actors inside and outside the organization who have role to realize the performance of ID Card/Family Card and Birth Certificate Service Office in Residence of Sukoharjo. The result of the research shows the good performance of ID Card/ Family Card and Birth Certificate Service in United Service Office of the Residence of Sukoharjo. It is indicated by the increase of the productivity hand in hand with the increase of the service quality, the more responsive the organization to society aspiration, the consistency to the rules and the accountable og the organization. The good performance of the service organization definited by four factors : the structure of the organization, the technology used by the organization, the culture of the organization, and the stakeholder back-up of the organization. The aplication of clear structure and simple technology, the creating of healthy organization culture, and a good stakeholder back-up from inside and outside the organization proved able to increase the performance of the organization.